2011
DOI: 10.1016/j.actbio.2010.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Gel structure has an impact on pericellular and extracellular matrix deposition, which subsequently alters metabolic activities in chondrocyte-laden PEG hydrogels

Abstract: While designing poly(ethylene glycol) hydrogels with high moduli suitable for in situ placement is attractive for cartilage regeneration, the impact of a tighter crosslinked structure on the organization and deposition of matrix is not fully understood. The objectives for this study were to characterize the composition and spatial organization of neo-matrix as a function of gel crosslinking and study its impact on chondrocytes via anabolic and catabolic gene expressions and catabolic activity. Bovine articular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
105
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(113 citation statements)
references
References 61 publications
5
105
2
1
Order By: Relevance
“…2a). This matches the results previously reported in non-degradable elastic hydrogels 20 . Strikingly, as the rate of stress relaxation or creep was enhanced, greater areas of type-II collagen and aggrecan deposition and a more interconnected cartilage matrix were observed in the faster relaxing gels (Fig.…”
Section: Faster Relaxation or Greater Creep Promotes Enhanced Formatisupporting
confidence: 93%
See 3 more Smart Citations
“…2a). This matches the results previously reported in non-degradable elastic hydrogels 20 . Strikingly, as the rate of stress relaxation or creep was enhanced, greater areas of type-II collagen and aggrecan deposition and a more interconnected cartilage matrix were observed in the faster relaxing gels (Fig.…”
Section: Faster Relaxation or Greater Creep Promotes Enhanced Formatisupporting
confidence: 93%
“…The elastic moduli of the hydrogels used in these studies ranges from 2 kPa to 100 kPa 12,14,20,21 , which is comparable to the moduli of chondrocyte PCM, ranging from 10 kPa to 75 kPa 29 . Enhanced stiffness in covalently crosslinked PEG based hydrogels, found to exhibit minimal stress relaxation here, restricted production of sGAG and collagens, distribution of cartilage matrix, and proliferation of chondrocytes 20,21 . However, our work revealed that the impact of stiffness was dependent on hydrogel relaxation.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…One potential explanation for this is that diffusivity of biomolecules (such as TGF-β3) would be lower in the stiffer, denser 4 % hydrogels; however, these hydrogels are still 96 % fluid and are therefore not expected to significantly inhibit biomolecule diffusivity. While MSCs cannot directly adhere to agarose, and hence initially are unlikely to be able to sense their local stiffness, they rapidly synthesise fibronectin and other extracellular matrix components in hydrogel culture (Nicodemus et al, 2011;Parekh et al, 2011) to which they can adhere, which may provide them with a mechanism through which they can sense the stiffness of the surrounding hydrogel.…”
Section: Discussionmentioning
confidence: 99%